Cost-Effective Satellite Ground Stations in Real-World Development for Space Classrooms - Pirada Techavijit; Polkit Sukchalerm (My University, 2025)
This paper presents the development and outcomes of a cost-effective satellite ground station designed as a learning tool for satellite communication and wireless communication education. The study investigates accessible satellites and the methods for accessing them. The developed ground station has the capability to access satellites in the V, U, and L frequency bands, allowing it to receive a variety of satellite data. This includes full-disk meteorological images, high-resolution multispectral images, and scientific data from payloads of satellites in both low Earth orbit (LEO) and geostationary orbit (GEO). The ground station demonstrates capabilities similar to those of large organizations but at a significantly lower cost. This is achieved through a process of identifying educational requirements and optimizing the system for cost-efficiency. This paper presents the design demonstration, actual construction of the ground station, and results. Additionally, it compiles characteristics from real signal reception experiences from various satellites.
Keywords: Ground segment; Ground station; Communications satellite; Spacecraft Design and Technology